PERANCANGAN WEBSITE BERBASIS APLIKASI DENGAN FITUR NOTIFIKASI WHATSAPP UNTUK SISTEM DETEKSI JATUH - Nurhidayat, Muhammad Adi; Y. R, Azhar; De Fitrah, Figo Azzam; Suratman, Fiky Y.; Istiqomah, Istiqomah (Telkom University, 2023)
This journal discusses the development of a fall detection system using radar as a sensor. The purpose of this system goes beyond technological advancement; it carries significant social impact. It aims to detect fall accidents early and provide prompt intervention to individuals, especially those living alone. In an effort to save lives and reduce the burden on caregivers. The system is connected to an IoT platform and a web-based application that allows users to view real-time detection results. With a notification feature that sends alerts to users and hospitals in the event of a fatal fall accident, this system plays a crucial role in improving the safety and quality of life for those in need. Through testing using the Blackbox Testing method with various scenarios, the system ensures it meets the set requirements and objectives, providing a positive user experience that aligns with expectations, and contributing to ongoing technological development. Key Words: web-based application, fall detection, notifications.